Pitch-side Acute Severe Pain Management Decisions in European Elite Football - Doheny, Maeve Claire; Bury, Gerard (International Journal of Sports Medicine, 2021)
This is the first study on acute severe pain management involving sport and exercise medicine Doctors who are leaders in football medicine in their respective countries. An online survey was designed describing the management of acute severe pain in this expert cohort. The survey captured participant sex, age, years working in sports medicine, core specialty and use of clinical practice guidelines (CPGs). Finally, three clinical vignettes exploring the management of acute pain were presented. Forty-four senior team doctors across 55 European countries completed the survey. There were no consistent guidelines proposed, with 33 (75%) participants indicating they did not use any. Methoxyflurane was proposed by 14 (32%) and 13 (30%) participants for female anterior cruciate ligament rupture and male ankle fracture, respectively. Strong opioids were not used in 17 (39%) and 6 (14%) participants regarding female cruciate injuries and male fractures, respectively. Despite 75% of participants having paediatric life support training, eight (18%) participants expressed uncertainty administering medications in this population, and 15 (34%) would avoid using strong opioids altogether. There is a tendency to undertreat pain and avoid strong opioids for reasons including lack of monitoring equipment, anti-doping concerns and lack of comfort treating paediatric patients with opioids.
Keywords: acute severe pain; pain management; acute pain management; pitchside emergency care; acute trauma care; football medicine